Student-teacher relationship and classroom goal structure profiles: Promoting achievement and preventing externalizing and internalizing behaviors. (December 2022) - Gallo, Angela; Olivier, Elizabeth; Archambault, Isabelle; Morin, Alexandre J.S.
Abstract: This study investigates which profiles, defined based on students reports of student-teacher relationships (closeness; conflict) and classroom goal structures (mastery; performance), were optimal to support adjustment (externalizing and internalizing behaviors) and achievement in Math and Language. Elementary students (Grades 3–6, N = 703) and their teachers ( N = 33) completed questionnaires in November 2011 and April 2012. Latent profile analysis identified four profiles, replicated across boys and girls: Average (44.46%), Mastery-Closeness (39.13%), Conflict (6.49%), and Approach-Closeness (9.92%). Students from the Conflict profile displayed more externalizing and internalizing behaviors than other students, whereas those from the Mastery-Closeness and Approach-Closeness profiles displayed the least difficulties. Students from the Approach-Closeness profile displayed the lowest achievement at the beginning of the year but the steepest increase over time. Highlights: We identify profiles of student-teacher relationships and classroom goal structures. The profiles were similar for boys and girls. The profiles were linked with achievement and externalizing/internalizing behaviors. Combining closeness and mastery with or without performance goals was optimal. The Conflict profile was the least optimal.